Unfolding the Leaf: A Comprehensive Insight into Phyllodes Tumors of the Breast: A Review Article - Sajan, Cyril (Asian Journal of Pharmaceutics (AJP), 2025)
Phyllodes tumors (PTs) are uncommon fibroepithelial lesions of the breast that comprise <1% of all breast neoplasms. These tumors are characterized by a distinctive histological pattern resembling a “leaf-like” architecture, arising from a biphasic proliferation of stromal and epithelial components. PTs are classified into benign, borderline, and malignant subtypes based on histological features, such as stromal cellularity, atypia, mitotic activity, tumor margins, and stromal overgrowth. While the majority is benign, all variants have the potential for local recurrence and, in the case of malignant types, distant metastasis. Their clinical and radiologic presentation often overlaps with fibroadenomas, making accurate pre-operative diagnosis challenging. The etiology of PTs remains poorly understood, although genetic mutations and hormonal influences are suspected to contribute. Surgical excision with wide margins remains the cornerstone of treatment, as incomplete resection is associated with a higher risk of recurrence. The role of adjuvant radiotherapy and chemotherapy remains limited and is generally reserved for high-risk or recurrent malignant cases. Prognosis depends primarily on histological classification, surgical margins, and the presence or absence of metastasis. This review provides a comprehensive overview of the present knowledge surrounding the epidemiology, pathogenesis, histopathology, classification, and management of PTs. Emphasis is placed on the importance of accurate diagnosis and appropriate surgical planning to reduce recurrence risk. In addition, the article explores evolving clinical guidelines and highlights areas requiring further research, aiming to support evidence-based practice and improved patient care in breast oncology.